Riverine microplastics: Behaviour, spatio-temporal variability, and recommendations for standardised sampling and monitoring. (December 2020) - Skalska, Karolina; Ockelford, Annie; Ebdon, James E.; Cundy, Andrew B.
Abstract: Microplastics (synthetic polymer particles <5 mm in size) are currently of major research interest due to their ubiquity and persistence in the environment, as well as their alleged adverse impact on aquatic biota. Although most research to date has targeted microplastic pollution within the marine environment, riverine pathways deliver up to 80 % of plastic debris into the seas and oceans. The transfer mechanisms of microplastics through river systems, however, remain largely understudied. A number of authors have attempted to assess the fate of plastic particles in river systems, often reporting contrasting findings. This is mainly due to the heterogeneity of river systems combined with a lack of standardisation between the sampling protocols adopted. Here, we summarise the current state of knowledge on the riverine transport pathways of plastic debris and examine the typical spatio-temporal patterns in microplastic occurrence in river waters and sediments. Furthermore, we critically evaluate the commonly used sampling techniques and provide guidelines for unified field study design. Lastly, we identify issues that warrant further research and propose recommendations for future studies to improve our understanding of microplastics in the riverine environment. Standardisation of sampling methods will be vital for the development of a more reliable microplastic monitoring strategy and, on a longer timescale, the implementation of appropriate mitigation measures.